Antimicrobial activity of selected South African medicinal plants - Nielsen, Trine R H (BioMed Central, 2012)
BACKGROUND: Nearly 3,000 plant species are used as medicines in South Africa, with approximately 350 species forming the most commonly traded and used medicinal plants. In the present study, twelve South African medicinal plants were selected and tested for their antimicrobial activities against eight microbial species belonging to fungi, Mycobacteria, Gram-positive and Gram-negative bacteria. METHODS: The radiometric respiratory technique using the BACTEC 460 system was used for susceptibility testing against Mycobacterium tuberculosis, and the liquid micro-broth dilution was used for other antimicrobial assays. RESULTS: The results of the minimal inhibitory concentration (MIC) determinations indicated that the methanol extracts from Acacia karoo, Erythrophleum lasianthum and Salvia africana were able to prevent the growth of all the tested microorganisms. All other samples showed selective activities. MIC values below 100 μg/ml were recorded with A. karoo, C. dentate, E. lasianthum, P. obligun and S. africana on at least one of the nine tested microorganisms. The best activity (MIC value of 39.06 μg/ml) was noted with S. africana against E. coli, S. aureus and M. audouinii, and Knowltonia vesitoria against M. tuberculosis. CONCLUSION: The overall results of the present work provide baseline information for the possible use of the studied South African plant extracts in the treatment of microbial infections.